Access to Essential Contraception, Family Planning, and Safe Motherhood Services During COVID-19 Pandemic: Single Secondary Level Care Hospital Experience - Biswas, Jayanta Kumar; Poddar, Soumen Das; Saravagi, Ganesh; Nilakantan , Ajith (Gynecology Obstetrics & Reproductive Medicine, 2022)
OBJECTIVE: During the COVID-19 pandemic, more precisely as a result of restrictions on movement and continuing altered perception of essential health care services, women’s health is disproportionately affected due to reduced access to services as per reports and statements made by different global and national level Government and non-government agencies. We aimed to evaluate the health care impacts related to contraception, family planning, and safe motherhood in an Indian Armed Forces secondary level care hospital during the COVID-19 pandemic. STUDY DESIGN: Immediate health care effect on women’s sexual and reproductive life during pandemic months (April to August of the year 2020) is analyzed through a retrospective observational cohort study in a single Indian Armed Forces secondary level care hospital experience. RESULTS: It has shown more late reported unintended pregnancies requiring surgical intervention, more late-registered antenatal cases and consequently delayed essential evaluations, increased trend in high-risk cases requiring in-patient care (IPD), and reduced access to contraception and family planning services in comparison to those in the previous two years. CONCLUSION: Considering these negative impacts noted in this observation, with the help of policymakers, government, and other non-government agencies, all services should be made available to women including un-interrupted out-patient (OPD) and IPD services in all hospitals, along with continued basic infection prevention and control precautions (IPC) to both clientele and health care workers (HCW). Telemedicine can also play a supplementary role in various aspects of women’s health to avoid upcoming population explosion and for better maternal-child health care.